Outcomes of Subfascial, Suprafascial, and Super-Thin Anterolateral Thigh Flaps: Tailoring Thickness without Added Morbidity - Diamond, Shawn; Seth, Akhil K.; Chattha, Anmol S.; Iorio, Mathew L. (Journal of Reconstructive Microsurgery, 2018)
Background Subfascial anterolateral thigh (ALT) flap thickness can be problematic with regards to bulk, oral competence, shoe-fit, or as a potential source of recurrent wound breakdown. We have utilized distinct upper thigh fascial planes to fashion thin (suprafascial) or super-thin (periscarpal) ALT flaps to improve surface topography. We compared outcomes based on ALT flap thickness to determine any significant differences in extremity coverage and reconstruction.Methods Analysis was completed on patients who consecutively underwent ALT free tissue transfer at a single institution from May 2012 to January 2017. Patient's operative, and postoperative characteristics were evaluated. Univariate analysis determined differences among matching as well as functional outcomes. A multivariable regression identified independent risk factors associated with patient, donor site, and flap complications.Results Fifty-one patients met inclusion criteria. Of these, 16 (31.4%) underwent traditional subfascial ALT flaps, and 35 (68.6%) underwent suprafascial (N = 23) or super-thin (N = 12) flaps. Thin flap patients were more likely to use tobacco (42.9% versus 6.3%; p < 0.01), have fewer perforators (1.20 ± 0.41 versus 1.64 ± 0.63; p < 0.009), and shorter mean operative times (425.9 ± 87.8 versus 511.9 ± 79.9; p < 0.002), but nearly identical flap sizes (163 cm2 versus 168 cm2). There were no significant differences in flap complications (18% versus 22%) or donor-site complications (6.3% versus 5.7%) between the thick and thin cohorts, respectively (p > 0.05). In subgroup analysis, diabetes mellitus was an independent risk factor for donor site morbidity (odds ratio [OR] = 1.23; p = 0.027) for all groups, whereas tobacco use and obesity (body mass index [BMI] > 30) failed to significantly alter outcomes independently.Conclusions Tailoring ALT thickness can be performed safely without compromising flap outcomes or patient morbidity. Suprafascial and super-thin ALTs allowed for safe, precise solutions for tissue coverage.
Keywords: ALT; anterolateral; suprafascial; super-thin; harvest plane; lower extremity reconstruction